A new epiphytic species of Notopleura (Rubiaceae) from Chucantí Nature Reserve, eastern Panama. Issue 2 (3rd July 2018) - Flores, Rodolfo; M. Taylor, Charlotte; McPherson, Gordon; Ibáñez, Alicia
ABSTRACT: The new species Notopleura sallydavidsoniae R.Flores & C.M.Taylor is here described and illustrated. It can be recognised by the following combination of characters: epiphytic habit, succulent stems and leaves, stipules sheathing at base and free portion ligulate with c. 8–10 glandular setae or appendages, well-developed bracts, five-merous flowers, rather well-developed calyx and fruits with two pyrenes. Eastern Panama is not well known botanically, but is part of the region that is the centre of species diversity for the epiphytic subgenus of Notopleura as well as for the genus overall.